2019
DOI: 10.1136/bmjopen-2019-033379
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a prospective, observational cohort study of awareness in mechanically ventilated patients admitted from the emergency department: the ED-AWARENESS study

Abstract: IntroductionAwareness with paralysis is a complication with potentially devastating psychological consequences for mechanically ventilated patients. While rigorous investigation into awareness has occurred for operating room patients, little attention has been paid outside of this domain. Mechanically ventilated patients in the emergency department (ED) have been historically managed in a way that predisposes them to awareness events: high incidence of neuromuscular blockade use, underdosing of analgesia and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Prior ED-based sedation research demonstrated clinical practice patterns placing patients at high risk for AWP (12,13,(15)(16)(17)(18)(19)(20)61). Given this, the severe psychologic trauma that can result from AWP, and the paucity of ED-based data, we previously conducted the ED-AWARENESS Study to rigorously assess this complication in mechanically ventilated ED patients (22,23). In that study, 2.9% of patients that were given neuromuscular blockers experienced AWP, with a higher proportion of AWP among patients exposed to rocuronium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior ED-based sedation research demonstrated clinical practice patterns placing patients at high risk for AWP (12,13,(15)(16)(17)(18)(19)(20)61). Given this, the severe psychologic trauma that can result from AWP, and the paucity of ED-based data, we previously conducted the ED-AWARENESS Study to rigorously assess this complication in mechanically ventilated ED patients (22,23). In that study, 2.9% of patients that were given neuromuscular blockers experienced AWP, with a higher proportion of AWP among patients exposed to rocuronium.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size rationale was based off of the parent trial (26). Based on our prior work regarding AWP in mechanically ventilated ED patients, we were confident during the planning of the trial that enough AWP events would be detected in order to conduct analyses with sufficient precision (22, 23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to clinical outcomes, the analysis compared outcomes between patients in each intervention period. Data from the ED-AWARENESS Study were excluded from outcome analyses, as survival to extubation was a key inclusion criteria of that study (18, 25). This resulted in a comparatively less critically ill cohort, which would bias clinical outcome results in favor of the intervention period.…”
Section: Methodsmentioning
confidence: 99%